Gender differences in fatigability and muscle activity responses to a short-cycle repetitive task - Srinivasan, D.; Sinden, K.; Mathiassen, Svend; Côté, J. (Springer-Verlag, 2016)
© 2016, The Author(s). Purpose: Epidemiological research has identified women to be more susceptible to developing neck–shoulder musculoskeletal disorders when performing low-force, repetitive work tasks. Whether this is attributable to gender differences in fatig ability and motor control is currently unclear. This study investigated the extent to which women differ from men in fatigability and motor control while performing a short-cycle repetitive task. Methods: 113 healthy young adults (58 women, 55 men) performed a standardized repetitive pointing task. The task was terminated when the subject’s perceived exertion reached 8 on the Borg scale. The time to task termination, and changes in means and cycle-to-cycle variabilities of surface electromyography signals from start to end of the task, were compared between women and men, for the upper trapezius, anterior deltoid, biceps and triceps muscles. Results: Women and men terminated the task after 6.5 (SD 3.75) and 7 (SD 4) min on average (p  >  0.05). All four muscles showed an increase of 25–35 % in average muscle activity with fatigue (no significant sex differences). However, men exhibited a higher increase than women in trapezius muscle variability with fatigue (31 vs. 7 %; p  <  0.05), and a decrease in biceps muscle variability where women had an increase (-23 vs. 12 %; p  <  0.05). Conclusions: Our results suggest that women and men may not differ in the ability to perform repetitive tasks at low-to-moderate force levels. However, differences in motor control strategies employed in task performance may explain gender differences in susceptibility to developing musculoskeletal disorders when performing repetitive work for prolonged periods in occupational life.